Islamic texts refer to psychosomatic illnesses: Historical comparison - Aloshari, Faisal Qasem (Journal of Educational and Psychological Sciences, 2023)
There is a recurring dilemma among doctors and health care providers in distinguishing between what is physical and what is psychological, such as the psychosomatic symptoms that lead sufferers to medical clinics. This confusion causes poor diagnosis on the one hand and causes poor therapeutic management on the other hand due to differences in treatment. Therapeutic approaches and methods (Khamis, 2018). Because the nature of the human sciences is participatory, this research aimed to draw a comparison between the view of early Muslim scholars on the nature of psychosomatic diseases and the view of modern psychology on these illnesses through comparison with Islamic historical texts, and the research showed that there are points of agreement and points of difference. One of the most prominent points of agreement between the two approaches is that the body is affected by the psychological state in what is known as psychosomatic illness, while we find that the most prominent points of difference are in Islamic psychology’s view of man as an integrated being, where religion is considered a central factor in influencing him, while Western psychology views man as a person isolated from religion. The research recommended further discovery of similarities and differences to reach an integrative vision for therapeutic psychology.
Keywords: Psychosomatic disorders; somatization disorders; Islamic psychology